A robust strategy for crafting monodisperse Li4Ti5O12 nanospheres as superior rate anode for lithium ion batteries. (March 2016) - Wang, Chao; Wang, Shuan; Tang, Linkai; He, Yan-Bing; Gan, Lin; Li, Jia; Du, Hongda; Li, Baohua; Lin, Zhiqun; Kang, Feiyu
Abstract: The ability to synthesizing monodisperse Li4 Ti5 O12 (LTO) nanospheres is the key to reducing the irreversible capacity of LTO materials, and thus improving their power performance. However, it remains a grand challenge to achieve uniform precursors of LTO nanospheres and maintain their spherical structures after annealing. Herein, we develop a robust strategy for the synthesis of monodisperse LTO nanospheres with an average diameter of 120 nm via the use of titanium nitride (TiN) as a titanium source for lithium ion batteries (LIBs). The precursors composed of uniform TiO2 /Li + nanospheres were formed in a stable alkaline environment during the course of heating of the solution of peroxo-titanium complex as a result of the dissolution of TiN, while TiO2 /Li + microspheres were easily yielded with the decrease in pH value of the precursor solution. The OH − anion was found to effectively retard the hydrolysis of peroxo-titanium complex as well as the aggregation of TiO2 /Li + nanoparticles. Intriguingly, a uniform polyvinyl pyrrolidone (PVP) layer formed in-situ on the surface of TiO2 /Li + nanospheres rendered LTO to retain the monodisperse spherical morphology after annealing. Notably, the as-prepared monodisperse LTO nanospheres comprised of the interconnected LTO nanograins with an average size of 15 nm uniformly coated by a carbon layer derived from the carbonization of PVP exhibited a high tap density (1.1 g cm −3 ) and an outstanding rate-cycling capability. The charge specific capacities at 1, 10, 50 and 80 C were 159.5, 151.1, 128.8 and 108.9 mAh g −1, respectively. More importantly, the capacity retention after 500 cycles at 10 C was as high as 92.6%. This work opens up an avenue to craft the uniform precursors of LTO and thus monodisperse LTO nanospheres that possess superior rate performance with high volumetric energy densities and long-term cyclic stability. Graphical abstract: Highlights: Monodisperse Li4 Ti5 O12 (LTO) nanospheres are crafted using TiN by the pH regulation. Alkali environment effectively controls the formation of TiO2 /Li + nanospheres. LTO can maintain the nanospheres by polyvinyl pyrrolidone coating layer. The LTO nanospheres show high taping density and excellent performance.